INDEKS GLISEMIK KACANG-KACANGAN [Glycemic Index of Selected Legumes] - Y. Marsono; P. Wiyono; Zuheid Noor (Jurnal Teknologi dan Industri Pangan, 2002)
Nutritional management for diabetic patients based on selection of low available carbohydrate foods has been criticized because the same availability of carbohydrate in different foods may result in different degree of glycemic response. This management is now being corrected by additional aid in selecting foods with the glycemic index (GI) of foods. GI is a measure of the glycemic response to the carbohydrate component within a food relative to the response to an equal carbohydrate portion of reference food (glucose or white bread). In Indonesia, data of the glycemic index of foods is still very limited. The objectives of the research are to provide GI of selected legumes, including red bean (Vigna umbellata), Mung bean (Phaseolus aureus), cow pea (Vigna sinensis ENDL), pigeon pea (Cajanus cajan MILLSPAUGH), edible podded peas (Pisum sativum LINN) and soy bean (Glycine max MERR). Eleventh health and normal volunteers (not diabetic) were provided. The volunteers took an overnight fasting, blood were drawn in the morning and analyzed for serum glucose. Then they were given the test legumes containing total carbohydrates equivalent to 25-g glucose to be consumed. Blood samples were drawn for glucose measurement every 30 minutes until 120 min after meal. Serum glucose was determined enzymatically and the glucose responses were drawn graphically. The GI of the beans studied was lowest for red bean (26) and highest for mung bean (76), Edible podded pea and soy bean had similar value of GI i.e. 30 and 31; whereas pigeon and cow pea had a higher value i.e. 35 and 51, respectively.